A Model for Communication in Information Technology Classes - Toni Chehlarova; Ivan Petkov (Педагогически форум)
A model for communication in information technology classes and the technology for its creation is presented. The applications of the model when using a webinar in class, as well as using a real contests and competitions to present a created product are shown.